Knowledge sharing from the perspective of Middle Eastern doctoral students studying in a Malaysian Islamic university - Sadeq, Abdullah I A; Mhd. Sarif, Suhaimi; Juhdi, Nurita; Abdul Hamid, Zabeda (2023)
People have various motivations for pursuing higher education in foreign countries. One prominent reason is the desire to acquire knowledge and experience that may be lacking in their home country. Another significant motivation is the aspiration to share this newfound knowledge with others. The primary objective of this research is to investigate the perspectives on knowledge sharing among university students. To achieve this goal, interviews were conducted with five doctoral students hailing from five Middle Eastern countries, all enrolled in an Islamic university in Malaysia. These interviews aimed to capture their insights and viewpoints regarding knowledge sharing. The outcomes of this study provide valuable insights for university boards of governors and management. They can use these insights to identify areas of focus that can enhance knowledge sharing among students while creating an environment conducive to fostering this exchange. Additionally, such improvements can contribute to enhancing the reputation and standing of the universities. Importantly, this aligns with Sustainability Development Goal number 4, which focuses on Quality Education. Furthermore, the findings of this research hold particular significance for Muslim nations. Future research endeavors should consider expanding the participant pool to include more doctoral students and their supervisors. This expansion can provide a more comprehensive understanding and deeper insights into knowledge sharing within academic settings.